2017
DOI: 10.1111/cpf.12483
|View full text |Cite
|
Sign up to set email alerts
|

Gender aspects on exercise‐induced ECG changes in relation to scintigraphic evidence of myocardial ischaemia

Abstract: In patients who have performed EST in conjunction with MPS, there is a gender difference in the diagnostic performance of ST response at stress, with a significantly lower PPV in females compared to males. For both genders, specificity can be significantly improved, and a higher PPV can be obtained, while the sensitivity might be compromised by considering more EST variables, in addition to the ST response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 38 publications
(46 reference statements)
2
3
1
1
Order By: Relevance
“…Our findings are of clinical importance because EST is one of the most commonly performed tests in clinical cardiology, and in many parts of the world the predominant test for the assessment of patients with suspected myocardial ischaemia. 2 Our study indicates a similar poor sensitivity and specificity for conventional EST as reported in previous studies 5,6 and demonstrates how the combination of HF-QRS and conventional ST-segment changes as markers of altered de- and repolarization, used in conjunction with all other clinical information, has the potential to improve the currently only modest diagnostic accuracy of EST. The algorithm, used in conjunction with all other available clinical information, could assist in clinical decision making and provide guidance for patients in the ‘rule-in’ and for patients in the ‘rule-out’ group, while patients in the intermediate zone do not directly benefit from the algorithm and certainly need additional testing.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Our findings are of clinical importance because EST is one of the most commonly performed tests in clinical cardiology, and in many parts of the world the predominant test for the assessment of patients with suspected myocardial ischaemia. 2 Our study indicates a similar poor sensitivity and specificity for conventional EST as reported in previous studies 5,6 and demonstrates how the combination of HF-QRS and conventional ST-segment changes as markers of altered de- and repolarization, used in conjunction with all other clinical information, has the potential to improve the currently only modest diagnostic accuracy of EST. The algorithm, used in conjunction with all other available clinical information, could assist in clinical decision making and provide guidance for patients in the ‘rule-in’ and for patients in the ‘rule-out’ group, while patients in the intermediate zone do not directly benefit from the algorithm and certainly need additional testing.…”
Section: Discussionsupporting
confidence: 76%
“…2,4 Although widely recommended and used as the first step in the work-up in intermediate risk patients, 2 the diagnostic accuracy of conventional EST is relatively low and limits its utility. 5,6 Sensitivity of EST lies at 33-50% and specificity at 84-96%. [7][8][9] Imaging modalities provide higher diagnostic accuracy and are increasingly recommended in several guidelines.…”
Section: Introductionmentioning
confidence: 99%
“…Despite its cost‐effectiveness and noninvasive nature, its clinical utility in this context is progressively declining. Our study reiterates the previously reported inadequate sensitivity and specificity of conventional ST‐segment analysis 3–6 . In contrast, HF‐QRS analysis, which primarily focuses on depolarization abnormalities, manifested superior sensitivity, higher positive likelihood ratio, and lower negative likelihood ratio for CAD detection compared to conventional ST‐segment analysis in our study.…”
Section: Discussionsupporting
confidence: 87%
“…Our study reiterates the previously reported inadequate sensitivity and specificity of conventional ST-segment analysis. [3][4][5][6] In contrast, HF-QRS analysis, which primarily focuses on depolarization abnormalities, manifested superior sensitivity, higher positive likelihood ratio, and lower negative likelihood ratio for CAD detection compared to conventional ST-segment analysis in our study. This aligns with previous reports on the performance of HF-QRS, which used MPI as the gold standard for CAD.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation